Social Media as a Village Government Communication Channel in Improving Public Services to the Community in Minahasa Regency - Kalesaran, Edmon Royan; Rondonuwu, Sintje Aneke; Rembang , Meiske M. (Journal of Management and Administration Provision, 2024)
Public service issues are still often the main topic in society, starting from the lack of clear information and slow service that occurs in government in various cases, both related to information, administration and implementation of development in various fields, to the lack of resources that are able to provide the best service to the community. The current era of information technology, new media, which includes social media, is certainly one of the right solutions in overcoming communication and information problems for the government, but the problem is whether social media has been used optimally in carrying out public service duties by the government, especially the government in the village. Along with the many complaints from the public regarding government services, even though communication and information technology is already present in the midst of society and the government. This is the basis of this study, to be studied and studied in more depth, using a qualitative research approach, related to how social media becomes a communication channel for village governments in improving public services. Village governments in Minahasa Regency, North Sulawesi Province have not optimally used social media as an information channel in an effort to improve public services. This is evidenced by the lack of official social media from the village government as a media/information channel in supporting public services. Not all village governments have the human resource capabilities that can manage and operate social media well, actively and intensively in providing information to the public regarding programs, policies, and government regulations. Most village governments in Minahasa Regency do not yet have official social media as a medium/channel of information to the public. There are still many village government officials who use their personal social media for the needs of conveying information to the public, even then only when necessary. Obstacles to the Village Government in utilizing social media to improve public services include limited human resources, technological infrastructure, and cultural constraints, these factors affect the effectiveness of communication through social media.